Rheological Investigation Of Stainless Steel Powder In Bimodal Particle Size Distribution - Jamaludin, Khairur Rijal; Muhamad, Norhamidi; M. Amin, Sri Yulis; Ab. Rahman, Mohd Nizam; Murtadhahadi, Ibrahim (Pusat Kajian Industri, Jurusan Teknik Kimia, Falkutas Teknik, Universitas Syiah Kuala Banda Aceh, Indonesia, 2006)
The rheological properties of the monomodal and bimodal MIM feedstock are presented. Stainless steel powder with particle size of 31 and 16 micron were mixed with PMMA/PEG and stearic acid to form a homogenous paste, which called feedstocks. Bimodal powders were blend at 30 to 70 % of the coarse powder distribution. Monomodal feedstock exhibits higher viscosity over the bimodal feedstocks. Binder separation is likely to occur in the monomodal feedstocks prepared with coarse powder especially at high temperature. Furthermore, bimodal feedstocks were less viscous than the monomodal but the particle size distribution has shown its influence to viscosity. The flow behavior index were decreasing when the temperature were increases. The investigation also discovered that the feedstock flow sensitivity was depends on the fine powder distributions in the feedstocks. Since all feedstocks demonstrate good pseudoplastic behavior, the feedstocks were suitable to be injection molded.